Antifungal and antibacterial effect of mouthwash of ethanolic extract of Psidium guajava L. on Candida albicans and Streptococcus mutans - Ortega-Buitrón, Marisol Rossana (2020)
Objective. To determine the antimycotic and antibacterial effect of Psidium guajavaL., at 50% and 90% on Candida albicans and Streptococcus mutans. Methods. In vitro experimental study where 32 units of analysis were included (Petri dishes with strains of Candida albicans or Streptococcus mutans of which 16 samples corresponded to the four study groups of the Candida albicansstrain and 16 samples for the four groups of the strains of Streptococcus mutans, the positive control group (2% Chlorhexidine or Nystatin 100,000 IU) and the negative control group (distilled water). Antifungal and antibacterial effect was determined by quantifying the diameter of inhibition halo. For analysis of the data, Tukey test was used in ANOVA. Results.Psidium guajavaL. 90% had a greater diameter of formation of the halo of mean inhibition 14.40 ± 2.06 mm compared to Streptococcus mutans and a mean of 13.50 ± 1.50 mm compared to Candida albicans. Regarding Psidium guajava L. 50%, the mean diameter of inhibition halo was 11.30 ± 1.76 mm and compared to Candida albincas, mean was 8.40 ± 2.22 mm. Finding statistically significant differences (p <0.05) of the antifungal and antibacterial effect of Psidium guajava L. on Candida albicans and Streptococcus mutans between the four groups studied (p = 0.00). Conclusions. The application of mouthwash based on ethanolic extract of Psidium guajava L., 90% has a greater antifungal and antibacterial effect in the treatment of candidiasis of the oral mucosa